2020
DOI: 10.3390/en13092184
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings Associated with the Use of Fly Ash and Nanoadditives in the Cement Composition

Abstract: The paper presented herein investigates the effects of using supplementary cementitious materials (SCMs) in quaternary mixtures on the compressive strength and splitting tensile strength of plain concrete. In addition, environmental benefits resulting from the proposed solutions were analysed. A total of four concrete mixtures were designed, having a constant water/binder ratio of 0.4 and total binder content of 352 kg/m3. The control mixture only contained ordinary Portland cement (OPC) as binder, whereas oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 103 publications
(171 reference statements)
0
35
0
Order By: Relevance
“…As a result of hydration, hydration products (calcium hydroxide, calcium silicate hydrate) are precipitated within the free spaces between the cement particles. This precipitation most likely contributes to increased separation between the CNFs in a twofold manner: (1) The distances between the CNFs may increase as a result of cement particle volume increase, associated with water binding and the precipitation of hydration products (amorphous calcium silicate hydrate and crystalline calcium hydroxide [35]) on their surface. (2) On the other hand, the nonconductive hydration products may precipitate in the spaces between fibers, leading to the loss of electric contact between them.…”
Section: Effect Of W/c Ratio and Pore Water Content On Bulk Resistivimentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of hydration, hydration products (calcium hydroxide, calcium silicate hydrate) are precipitated within the free spaces between the cement particles. This precipitation most likely contributes to increased separation between the CNFs in a twofold manner: (1) The distances between the CNFs may increase as a result of cement particle volume increase, associated with water binding and the precipitation of hydration products (amorphous calcium silicate hydrate and crystalline calcium hydroxide [35]) on their surface. (2) On the other hand, the nonconductive hydration products may precipitate in the spaces between fibers, leading to the loss of electric contact between them.…”
Section: Effect Of W/c Ratio and Pore Water Content On Bulk Resistivimentioning
confidence: 99%
“…Cement nanocomposites have recently gained much attention. Nanoparticles are added not only to engineer the mechanical properties [1][2][3][4] of the composites but also to render cement electrically conductive and responsive to mechanical load [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that adding blast furnace slag and fly ash could be useful in developing concrete resistance. However, the use of mineral admixtures is limited, and it is necessary to study improvement methods for general applications [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of rubber crumbs in the concrete asphalt mixture increases the plasticity of the whole mixture and protects the cured concrete from cracking and shrinkage under thermal expansion and contraction. In recent years, extensive researchers have performed studies on the use and application of rubber crumbs in concrete [3]. Studies on the rubber size effect on concrete strength properties have shown that, although the strength of the concrete containing rubber crumbs decreases compared to the mixtures made of aggregates, the plastic capacity of the concrete increases considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FA-based geopolymer binders display a reliable resilience to heat curing. Nevertheless, the main drawbacks associated with the application of FA are its poor strength when cured in ambient temperature, the high required molarity (UP 10 M) of sodium hydroxide, and high demand for an alkaline solution [22]. Accordingly, there is no benefit of using FA separately to achieve a satisfactory alkali-activated binder.…”
Section: Introductionmentioning
confidence: 99%